2012
DOI: 10.1007/s00125-012-2461-0
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Excess Weight Loss (DEWL) Trial: a randomised controlled trial of high-protein versus high-carbohydrate diets over 2 years in type 2 diabetes

Abstract: In a 'real-world' setting, prescription of an energy-reduced low-fat diet, with either increased protein or carbohydrate, results in similar modest losses in weight and waist circumference over 2 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(190 citation statements)
references
References 25 publications
4
176
0
10
Order By: Relevance
“…Specifically, significant reductions in HbA1c have been detected at 3 and 6 months using very low-carb or low-carb diets versus lowfat diets [47][48][49], even when there was no upper limit for SFA intake [44]. Similarly, Elhanyay et al found that a low-carb MD produced a greater improvement in HbA1c than a traditional MD or a low-fat diet at 1 year [43], whereas studies comparing diets with ≥40% carb percentage, differing mainly in protein and lipid content, have reported similar reduction rates of HbA1c at 1 year [42,45,50]. Finally, in the study by Shai et al, with a longer follow-up of 2 years, in the subgroup of individuals with diabetes, HbA1c decreased in the very low-carb group only, but not in the MD and low-fat group [27].…”
Section: Step 2: Does the Patient Have High Hba1c?mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, significant reductions in HbA1c have been detected at 3 and 6 months using very low-carb or low-carb diets versus lowfat diets [47][48][49], even when there was no upper limit for SFA intake [44]. Similarly, Elhanyay et al found that a low-carb MD produced a greater improvement in HbA1c than a traditional MD or a low-fat diet at 1 year [43], whereas studies comparing diets with ≥40% carb percentage, differing mainly in protein and lipid content, have reported similar reduction rates of HbA1c at 1 year [42,45,50]. Finally, in the study by Shai et al, with a longer follow-up of 2 years, in the subgroup of individuals with diabetes, HbA1c decreased in the very low-carb group only, but not in the MD and low-fat group [27].…”
Section: Step 2: Does the Patient Have High Hba1c?mentioning
confidence: 99%
“…Specifically, a Mediterranean diet (45% carbs, 40% lipids) achieved the same improvement in HDL as a low-fat diet (60% carbs, 25% lipids) [39], implying that moderate restriction of carbohydrates may not be enough. Finally, proteins per se do not seem to be responsible for the significant changes in lipid profile; i.e., similar changes in HDL, TG, total cholesterol (TC), and TC/HDL ratio were seen when two low-fat diets (30% lipids), high or low in protein (30% vs. 15%), were compared in overweight or obese individuals with type 2 diabetes, in 3 different studies at 1 year of follow-up [45,46,50].…”
Section: Step 4: Does the Patient Have A Disturbed Lipid Profile?mentioning
confidence: 99%
“…Eine erfolgreiche Gewichtsreduktion kann nur mit einer energiereduzierten Diät, die fettreduziert, aber auch kohlenhydratereduziert sein kann oder einem mediterranen Ernährungsmuster entspricht, erreicht werden [21,22,23]. Eine mediterrane Ernährung konnte darüber hinaus die Notwendigkeit der Verordnung oraler Antidiabetika bei neu diagnostizierten Diabetikern reduzieren [24].…”
Section: Implikationen Für Das Lebensstilmanagementunclassified
“…[49][50][51][52] It has been observed that a greater number of people are able to achieve weight loss of more than 10% of body weight 48 with diets moderately low in carbohydrate (eg, the South Beach diet) and during weight maintenance after weight loss these diets are more acceptable. 52,53 These studies suggest that maintenance of a reduction in energy intake remains the most critical factor in inducing weight loss but lower carbohydrate, higher protein diets may confer some advantage in improving compliance in the long-term.…”
Section: Weight Lossmentioning
confidence: 99%